Development of a Bionic Tube with High Bending-Stiffness Properties Based on Human Tibiofibular Shapes - Jianqiao Jin; Kunyang Wang; Lei Ren; Zhihui Qian; Xuewei Lu; Wei Liang; Xiaohan Xu; Shun Zhao; Di Zhao; Xu Wang; Luquan Ren (Biomimetics, 2023)
The human tibiofibular complex has undergone a long evolutionary process, giving its structure a high bearing-capacity. The distinct tibiofibular shape can be used in engineering to acquire excellent mechanical properties. In this paper, four types of bionic tubes were designed by extracting the dimensions of different cross-sections of human tibia–fibula. They had the same outer profiles, but different inner shapes. The concept of specific stiffness was introduced to evaluate the mechanical properties of the four tubes. Finite-element simulations and physical bending-tests using a universal testing machine were conducted, to compare their mechanical properties. The simulations showed that the type 2 bionic tube, i.e., the one closest to the human counterpart, obtained the largest specific-stiffness (ε = 6.46 × 104), followed by the type 4 (ε = 6.40 × 104) and the type 1 (ε = 6.39 × 104). The type 3 had the largest mass but the least stiffness (ε = 6.07 × 104). The specific stiffness of the type 2 bionic tube increased by approximately 25.8%, compared with that of the type 3. The physical tests depicted similar findings. This demonstrates that the bionic tube inspired by the human tibiofibular shape has excellent effectiveness and bending properties, and could be used in the fields of healthcare engineering, such as robotics and prosthetics.